Explicit group iterative methods for the solution of two-dimensional time-fractional telegraph equation - Ali, Ajmal; Ali, Norhashidah Hj Mohd (AIP conference proceedings, 2019)
In this work, we formulate two new four-point explicit group iterative schemes namely fractional explicit group (FEG) and fractional explicit de-coupled group (FEDG) iterative schemes in solving two-dimensional second-order time-fractional hyperbolic telegraph differential equation subject to specific initial and Dirichlet boundary conditions. Both explicit group numerical iterative schemes derived from the combination of standard and rotated (skewed) five-point Crank-Nicolson finite difference approximations. The results, derived from the conducted numerical experimentations, show that FEDG method has significantly least computational efforts in terms of execution of CPU-timings when compared with other iterative schemes in this paper.